Precompetitional weight reduction modifies prooxidative-antioxidative status in judokas - Knapik, K.; Sieron, K.; Wojtyna, E.; Onik, G.; Romuk, E.; Birkner, E.; Stanek, A.; Kawczyk-Krupka, A.; Plinta, R.; Sieron, A. (Oxidative Medicine and Cellular Longevity, 2019)
Objective. The main aim of the study was an assessment of the influence of rapid weight loss on oxidative stress parameters in judokas differing in weight reduction value. Materials and Methods. The study included 30 judokas with an age range of 18-30 years (mean age: 22 4±3 40 years). Enzymatic and nonenzymatic antioxidative markers, lipid peroxidation markers, and total oxidative stress were assessed three times: one week before a competition (the first stage), after gaining the desired weight (the second stage), and one week after the competition (the third stage). Results. Between the first and the second stage, the concentration of lipid hydroperoxides (LPH) decreased significantly. The superoxide dismutase (SOD), copper- and zinc-containing superoxide dismutase (Cu,Zn-SOD), ceruloplasmin (CER), malondialdehyde (MDA), LPH, and total oxidative stress (TOS) concentrations were the lowest one week after the competition. Linear regression indicated that the emphases on increased weight reduction increased the activity of glutathione peroxidase (GPx), glutathione reductase (GR), glutathione S-transferase (GST), and protein sulfhydryl (PSH) between the first and the second stage of the study. Moderate weight reduction (2-5%) resulted in elevated levels of SOD, Mn-SOD, LPH, MDA, and TOS in comparison to low and high reductions. An opposite relation was observed in PSH. In judokas, the precompetitional weight reduction range was 0.44-6.10% (mean: 2 93% ± 1 76%) of the initial body weight. Concentrations of superoxide dismutase (SOD; p < 01), manganesedependent superoxide dismutase (Mn-SOD; p < 001), and ceruloplasmin (CER; p < 05) decreased between the first and the third stage of the study as well between the second and third one. Before competitions, a decrease in lipid hydroperoxide (LPH; p < 01) concentration was observed. A reduction of malondialdehyde (MDA; p < 05), LPH (p < 01), and total oxidative stress (TOS; p < 05) levels between the first and the final stage occurred. The increase in weight reduction was linearly correlated with the rise of glutathione peroxidase (GPx; p < 05), glutathione reductase (GR; p < 05), glutathione Stransferase (GST; p < 05), and protein sulfhydryl (PSH; p < 05) concentrations between the first and the second stage of the study. Moderate weight reduction (2-5%) resulted in elevated levels of SOD (p < 05), Mn-SOD (p < 05), LPH (p < 05), MDA (p < 05), and TOS (p < 05) in comparison to low and high reductions. An opposite relation was observed in PSH (p < 005). Conclusions. The effect of weight reduction in judo athletes on prooxidative-antioxidative system diversity depends on the weight reduction value.